Ответ:
Пошаговое объяснение:
0,3а + 0,7а = а
2х - (х + 1) = 2х - х - 1 = х - 1
6х - 12 = 5х + 4
6х - 5х = 4 + 12
х = 16
4 + 25у = 6 + 24у
25у - 24у = 6 - 4
у = 2
-9а + 8 = -10а - 2
-9а + 10а = -2 - 8
а = -10
3(х - 5) - 2(х - 4) = 8
3х - 15 - 2х + 8 = 8
х - 7 = 8
х = 8 + 7
х = 15
0,5а - (0,3а + 1/2) + (3,8а - 8 1/2) = 0,5а - 0,3а - 0,5 + 3,8а - 8,5 = 4а - 9
пусть на втором катере х людей, тогда на первом 2х
2х - 98 = х - 16
2х - х = - 16 + 98
х = 82 человека на втором катере
2 * 82 = 164 человека на первом катере